Who Do Polls Really Influence? Survey Institutions and Mediatized Political Communication in Indonesia - Verdy Firmantoro; Syahirul Alim; Nisa Alfira; Fidzia Alima (ULTIMA Comm, 2025)
This research explores the response of Indonesian national poll organizations to the mediatization of public opinion polls within evolving political communication. Using a qualitative with phenomenological approach, interviews with senior researchers from four leading polling institutions consider how media interactions and the communication of survey results influence professional practices. The results find that polling organizations have a high degree of interdependence with news media. Pollsters adapt to media logic: they distill survey results into concise, news-friendly formats, while news organisations use polling data as reliable political information and for drawing public attention. Fear of misuse or manipulation of data may cause pollsters to withhold disclosure. And political elites respond more strongly to media exposure of polls than local-level voters, with survey results influencing party agendas and strategies rather than directly shaping voter preferences. In this regard, mediatization is a tool which can either bolster or erode democratic processes. News coverage of politicians in the media can amplify public discourse, but sensationalist coverage risks eroding public trust. The study stresses how better ethical norms need to be defined and that media literacy should be intensified, such that public opinion polls can contribute to ensuring sustainable democracy in Indonesia.